2010
DOI: 10.1007/s11325-010-0352-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of formulas predicting the optimal nasal continuous positive airway pressure in a Greek population

Abstract: We conclude that the level of CPAP necessary to abolish sleep apnea can be successfully predicted from both equations, using common clinical measurements and prediction formulas that may be useful in calculating the starting pressure for initiating CPAP titration. It may also be possible to shorten CPAP titration and perhaps in selected cases to combine it with the initial diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
1
25
0
7
Order By: Relevance
“…Many other prediction formulas are also available with respect to different ethnicity. [6][7][8][9][10][11] Previous reports of differences between predicting CPAP level and optimal CPAP pressure using manual titration revealed that 83% of patients were within ± 2 cm H2O and 95% were within ±3 cm H2O. 4,5 Chung-Chieh in his study observed automatic CPAP pressure was higher than predicted CPAP pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Many other prediction formulas are also available with respect to different ethnicity. [6][7][8][9][10][11] Previous reports of differences between predicting CPAP level and optimal CPAP pressure using manual titration revealed that 83% of patients were within ± 2 cm H2O and 95% were within ±3 cm H2O. 4,5 Chung-Chieh in his study observed automatic CPAP pressure was higher than predicted CPAP pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidelines [3], pressure prediction formulas [6,7], Clinical Decision Support Systems (CDSS) [2] and Artificial Intelligence techniques [8] suggested that there is no significant difference in clinical outcome between auto titration and algorithmically defined fixed pressure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of the present study and the rationale for another CPAP prediction formula was to investigate possible ethnicity-related effects, and thus create an improved prediction formula for the estimation of the optimum CPAP pressure. However, this underlying assumption was not proved in the course of this study, as there was no difference in the CPAP pressures between CPAP prediction formulas for Caucasians, Asians and Turkish patients, and the authors conclude that race/ ethnicity may not be an important factor in predicting CPAP levels.In the literature several formulas have been used with varying degrees of success to determine the optimal CPAP pressure [7,10,21,22]. Nahmias et al reported a formula including ideal body weight ratio, respiratory disturbance index (RDI) and nadir oxyhemoglobin saturation [21].…”
mentioning
confidence: 99%
“…In the literature several formulas have been used with varying degrees of success to determine the optimal CPAP pressure [7,10,21,22]. Nahmias et al reported a formula including ideal body weight ratio, respiratory disturbance index (RDI) and nadir oxyhemoglobin saturation [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation